2006
DOI: 10.1063/1.2198095
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically deposited zinc oxide arrays for field emission

Abstract: Periodic zinc oxide rod arrays were fabricated on patterned templates by electrochemical deposition and were employed as field emitters. The morphology and crystal structure of the zinc oxide array were examined by scanning electron microscopy and x-ray diffraction, respectively. The dependence of the field emission current density J and the applied electric field E presented a two-stage slope behavior in ln(J∕E2)−1∕E plot according to Fowler-Nordheim equation. The mechanism of the electron emission is attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 26 publications
5
47
1
Order By: Relevance
“…[1][2][3][4][5] It would therefore be of great practical interest to develop a lower temperature technique to synthesize ZnO nanostructures on lower cost substrates such as plastics for large-area applications. To date, only a few efforts have been made to characterize the FE properties of ZnO nanostructures obtained by low-temperature methods, [6][7][8][9][10] including the ZnO nanowire arrays synthesized by employing templates. 6,7 Although ZnO nanowires have also been grown successfully without templates by using an electrochemical technique, 8,[11][12][13] only one study has reported the FE properties of the electrodeposited material (with a high turn-on field).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] It would therefore be of great practical interest to develop a lower temperature technique to synthesize ZnO nanostructures on lower cost substrates such as plastics for large-area applications. To date, only a few efforts have been made to characterize the FE properties of ZnO nanostructures obtained by low-temperature methods, [6][7][8][9][10] including the ZnO nanowire arrays synthesized by employing templates. 6,7 Although ZnO nanowires have also been grown successfully without templates by using an electrochemical technique, 8,[11][12][13] only one study has reported the FE properties of the electrodeposited material (with a high turn-on field).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few efforts have been made to characterize the FE properties of ZnO nanostructures obtained by low-temperature methods, [6][7][8][9][10] including the ZnO nanowire arrays synthesized by employing templates. 6,7 Although ZnO nanowires have also been grown successfully without templates by using an electrochemical technique, 8,[11][12][13] only one study has reported the FE properties of the electrodeposited material (with a high turn-on field). 8 In the present work, we demonstrate the successful growth of two different ZnO nanostructures, nanopillars (1D) and nanowalls (2D), on a plastic substrate by using electrodeposition at low temperature (70°C) without templates.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2c shows a periodical ZnO nanorod array, which was created by electrochemical deposition using a patterned template. 15 Further, Fig. 2d exhibits ZnO nanotubes formed by hydrothermal decomposition.…”
Section: Fabricationmentioning
confidence: 97%
“…The fabrication conditions, crystal structures, and the growth mechanism of these ZnO nanostructures can be found elsewhere. 7,[14][15][16] The SEM images in Fig. 2 present some typical morphologies fabricated for FE study.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation